2021
DOI: 10.1186/s13000-021-01110-6
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of SS18-SSX antibody as a diagnostic marker for pulmonary metastatic synovial sarcoma

Abstract: Background The novel SS18-SSX fusion-specific antibody is reported to have high sensitivity and specificity for the diagnosis of primary synovial sarcoma (SS), which often metastasizes to the lung. Thus far, no study has validated the diagnostic efficacy of SS18-SSX antibody for pulmonary metastatic SS. Therefore, we aimed to investigate the usefulness of the SS18-SSX antibody in the diagnosis of pulmonary metastatic SS. Methods We evaluated the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
4
7
0
Order By: Relevance
“…Our study included 70 synovial sarcoma samples, 64 of which were positive cases (91%) by SS18-SSX IHC. This is concordant with published literature across 8 studies, which have recorded a total of 303 positive IHC results from 326 (93%) synovial sarcoma samples, with sensitivity ranging from 86 to 100% in their respective studies 14,20–26. Only one study attributed negative samples to a rare alternative fusion splice site, 23 while others alluded to technical factors arising from tissue handling 20,22,24.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study included 70 synovial sarcoma samples, 64 of which were positive cases (91%) by SS18-SSX IHC. This is concordant with published literature across 8 studies, which have recorded a total of 303 positive IHC results from 326 (93%) synovial sarcoma samples, with sensitivity ranging from 86 to 100% in their respective studies 14,20–26. Only one study attributed negative samples to a rare alternative fusion splice site, 23 while others alluded to technical factors arising from tissue handling 20,22,24.…”
Section: Discussionsupporting
confidence: 88%
“…This is concordant with published literature across 8 studies, which have recorded a total of 303 positive IHC results from 326 (93%) synovial sarcoma samples, with sensitivity ranging from 86 to 100% in their respective studies. 14,[20][21][22][23][24][25][26] Only one study attributed negative samples to a rare alternative fusion splice site, 23 while others alluded to technical factors arising from tissue handling. 20,22,24 Although we identified one technical false negative attributable to a freezing artifact, we were able to demonstrate that most cases are biological true negatives, where the fusion epitope is different from the one recognized by the diagnostic antibody.…”
Section: Discussionmentioning
confidence: 99%
“…The first goal we aimed at in this study was to confirm the high sensitivity and specificity of the SS18-SSX antibody in the diagnosis of SS in a retrospective cohort of SSs and its histological mimickers. Our results report a sensitivity of 95% and a specificity of 100% and are thus in perfect agreement with recently published data 13,17,19,22 27 . In the largest reported series (400 tumors including 100 SSs and 300 mimics), Baranov et al who suggested for the first time that the IHC approach could replace molecular investigations to support SS morphological diagnosis 19 have obtained values perfectly overlapping with those presently reported.…”
Section: Discussionsupporting
confidence: 93%
“…[14][15][16][17]19 TLE1 is usually focal and weak in LMS; however, can be diffuse in rare cases. 31 SS18-SSX IHC positivity is never reported in LMS . 26,31 Rhabdomyosarcoma has a myoD1 + /myogenin + /SS18-SSX-immunoprofile differentiating it from primary renal synovial sarcomas.…”
Section: Discussionmentioning
confidence: 93%